Opportunistic infections in systemic lupus erythematosus. (June 2012) - Sebastiani, Gian Domenico; Iuliano, Annamaria; Prevete, Immacolata; Minisola, Giovanni
Opportunistic infections (OIs) are not frequently seen in systemic lupus erythematosus (SLE). However, when present they are very dangerous, being potentially fatal in the majority of cases. Immunosuppressive therapy is the strongest risk factor for OI and correlates with death during infective episodes, but there are other factors predisposing to infection in SLE patients, such as several defects of the immune system that are intrinsic to the disease. The diagnosis of OI in SLE may be overlooked, owing to the fact that SLE flares may mimic infection with fever and inflammatory syndrome, and needs special attention in patients at risk. Finally, we have to consider that OIs could be a trigger of SLE too.